Ambrosia maritima L., Molluscicide végétal prometteur ! - Sidhom, MZ.; Geerts, S. (Tropicultura, 1983)
Ambrosia maritima L., a promising molluscicide of plant origin !. Masses of granivorous birds destroy about 5-10 % of the rice crop produced in the central Niger delta. To the local species (ducks, ploceid birds and the quelea, which is the most abundant and noxious pest with numbers ranging from 18 million in January to 10 million in May-June) add palearctic migratory birds, which are mainly ducks and stilt-birds. Bird control is necessarily undertaken but is inefficient due to the vastness of the region, difficult access to the sites, the number of birds and insufficient financial means.